Objective and Subjective Time in Death of a Salesman: A Cognitive-Neuropsychological Analysis of Memory and Temporal Perception - Mufeed F. Al-Abdullah (An Overview of Literature, Language and Education Research Vol. 8, 2024)
Arthur Miller in The Death of a Salesman, which is his implementation of the tragedy of the common man, skillfully utilizes the concepts of objective time and subjective time to build his plot which covers the last twenty-four hours in the life of the protagonist Willy Loman. The plot is constructed retrospectively by the use of memory. This study aims to analyze Arthur Miller’s utilization of objective time and subjective time in his tragedy of Death of a Salesman (1949). Objective time is related to events in the present, whereas subjective time is related to his memories of the past and predictions of the future. The study presents the concepts of objective time and subjective time in light of recent relevant neuropsychological studies and analyzes the text in light of them. Present events that belong to the objective sphere in the play are few and they make the backbone of the plot which covers the last two days in the life of the character. These events and the dialogs they stimulate belong to the domain of objective time. The memories these events and dialogs trigger belong to the domain of subjective time. Memories of past experiences and future predictions record the protagonist’s mental activities the mind moving back and forth in time which is either gone or has not come. Therefore, these memories cover the past life of sixty-three years of the protagonist, whereas the objective sphere covers the last 48 hours of the protagonist’s life. The method used in the study is a close textual study of the play in light of modern neuropsychological theories. The study divides the remembered life of the protagonist into three phases, namely his early years before he got his job as a salesman in Wagner’s company at the age of thirty-four; the second phase covers the years from thirty-four to fifty-one when his son discovers his illicit relationship with a woman in a hotel in Boston; and the last phase covers events till the beginning of the play. Noticeably, the character does not remember things in the order of their occurrence. Remembered events from the three stages are related randomly across the play. The study explains why the dramatist employs episodic memory in the first and third phases and future memory in the second phase to forecast future accomplishments and events. The researcher chooses to show how the writer used another branch of knowledge to further the field of drama and how his understanding of contemporary neuropsychological discoveries helped him create a complex and informed plot. Additionally, the study provides an explanation of the neuropsychological topics used.